Triumfetta multiglandulosa (Malvaceae, Grewioideae): A New Species from the Remnants of the Brazilian Atlantic Forest in the State of Goiás, Brazil - Fernandes Júnior, Aluisio J. (2018)
A new species of Triumfetta from the Brazilian Atlantic Forest is described and illustrated by line drawings and scanning electron micrographs, along with notes on taxonomy, morphology, geographic distribution, and conservation status. Triumfetta multiglandulosa (Malvaceae, Grewioideae) grows in disturbed areas on sandy soils in the state of Goiás in midwestern Brazil. It resembles Triumfetta dioica and T. mexiae especially due to the paniculiform inflorescence and fruits without uncinate spines, but differs by having the indumentumwith glandular trichomes, ovate stipules with a caudate apex, inflorescences with three-flowered cymes, 10 stamens, and entire stigmas. An identification key for all species of Triumfetta from Brazil is also provided.